SAT0168 What is the Treatment Durability and Safety Profile of Rheumatoid Arthritis Patients Treated with Infliximab Plus Methotrexate and/or Leflunomide? An Analysis from a Real-World Registry. (9th June 2015) - Faraawi, R.; Joshi, R.; Bensen, W.; Choquette, D.; Olszynski, W.; Arendse, R.; Sheriff, M.; Rahman, P.; Sampalis, J.; Rampakakis, E.; Tkaczyk, C.; Nantel, F.
Abstract : Objectives: Clinical trials of anti-TNF therapies have shown that concurrent methotrexate (MTX) therapy enhances the efficacy of TNF inhibitors. A scarcity of data exists on the benefits of combination therapy with IFX and MTX vs. leflunomide (LEF) in a real-world setting; therefore the BioTRAC Registry database was used to explore this question. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, AS, or PsA with IFX or golimumab as first biologics or after having been treated with a biologic for <6 months. RA patients treated with IFX who were enrolled between 2002-2014 were included in this analysis. Treatment durability was assessed with the Kaplan Meier (KM) estimator of the survival function and Cox regression. Results: 723 RA patients were included; at baseline 516 (71.4%) were on IFX+MTX, 115 (15.9%) on IFX+LEF, and 92 (12.7%) on IFX+MTX+LEF. The mean (SD) age was 55.5 (13.6) years, 76.2% were female and mean (SD) disease duration was 8.7 (9.2) years. The majority of patients were from Ontario (50.6%), followed by Western Canada (25.8%), and Quebec (20.9%). There were 217 (30.0%) patients who discontinued due to lack/loss of response, disease progression, adverse event (AE) or change in therapy with a KM-based mean (SE) time to discontinuation of 83.9 (3.0) months. Upon adjusting for potential confounders, higher durability was observed for the IFX+MTX group vs. IFX+LEF [hazard ratio -HR- (95% CI): 0.50 (0.25-1.01), P=0.055]. Moreover, factors independently associated with premature treatment termination were earlier enrolment period [HR2006-09 vs. 2002-05 (95% CI): 0.15 (0.02-1.15, P=0.068; HR2010-2014 vs. 2002-05 (95% CI): 0.09 (0.01-0.70), P=0.021], shorter baseline disease duration [HR (95% CI): 0.97 (0.93-1.00), P=0.054], and increased baseline pain levels [HR (95% CI): 1.14 (1.03-1.26), P=0.013]. 2, 016 AEs were reported by 343 patients (106.8 events/100 patient-years) and 156 SAEs by 96 patients (8.3 events/100 patient-years). The incidence density ratio (IDR) (95% CI) was higher in the groups IFX+MTX vs. IFX+LEF for both AEs and SAEs with 1.44 (1.25-1.67) and 1.60 (0.94-2.73), respectively, however the latter was not statistically significant. When examining the triple combination therapy (IFX+MTX+LEF), higher durability was observed compared to both IFX+MTX [HR (95% CI): 3.68 (1.14-11.92); P=0.030] and IFX+LEF [HR (95% CI): 6.34 (1.72-23.34); P=0.006]. Conclusions: The results of this real-world observational study have shown that combination therapy with IFX+MTX is associated with significantly higher treatment durability compared to IFX+LEF in RA patients with increased risk for AEs but not for SAEs. Disclosure of Interest: R. Faraawi Consultant for: Janssen, Speakers bureau: Janssen, R. Joshi: None declared, W. Bensen Consultant for: Janssen, D. Choquette Consultant for: AbbVie, Amgen, Celgene, BMS Canada, Janssen, Pfizer, W. Olszynski: None declared, R. Arendse Consultant for: Janssen, M. Sheriff: None declared, P. Rahman Consultant for: Abbott, AbbVie, Amgen, BMS, Celgene, Janssen, Novartis, Pfizer, Roche, J. Sampalis Shareholder of: JSS Medical Research, Employee of: JSS Medical Research, E. Rampakakis Employee of: JSS Medical Research, C. Tkaczyk Employee of: Janssen, F. Nantel: None declared